P11.46.A Whole exome sequencing identifies novel SLIT2 mutations in primary CNS lymphoma. (5th September 2022) - Kaulen, L D; Erson-Omay, E Z; Henegariu, O; Karschnia, P; Huttner, A; Günel, M; Baehring, J M
Abstract: Background: Whole exome sequencing (WES) data on primary CNS lymphoma (PCNSL) is scarce and correlation with clinical observations is needed to facilitate personalized care. Here we present WES data of six PCNSL and correlate genetic findings with clinical outcome. Material and Methods: WES was performed on paired blood and tumor DNA samples from six PCNSL patients to a median coverage of 100x (range: 73-135x) and 194x (range: 127-232x), respectively. Selected, novel mutations were validated with Sanger sequencing. Epstein-Barr virus (EBV) status was assessed in tumor tissue. Progression free survival (PFS) and overall survival (OS) were analyzed in our cohort and in an extension cohort from the cBio Cancer Genomics Portal using Kaplan-Meier method and log-rank tests. P values < 0.05 were considered significant. Results: We found a median of 22 (range: 11-68) somatic copy number variations, 171 (range: 82-298) somatic single-nucleotide variants and 11 (range: 0-22) somatic insertions/deletions per PCNSL. CDKN2A loss, identified in five samples, was the most commonly detected copy number alteration. PCNSL carried mutations in previously described PIM1, MYD88, CD79B or BTG genes. In three PCNSL, we identified novel SLIT2 mutations (p.N63S, p.T590M, p.T732S) clustered around the leucine-rich repeats (LRR) domains. WNT-reporter and NF-kB reporter luciferase assays suggested alterations were loss-of-function variants. SLIT2 mutations were associated with shorter PFS in our cohort and with shorter OS in an extension cohort of 1856 lymphoid malignancies from the cBio Cancer Genomics Portal. Conclusion: PCNSL harbored previously unknown SLIT2 mutations clustered around domains that are critical for interaction with ROBO proteins. SLIT2 mutations may be predictive of less favorable outcome in PCNSL. Additional clinical and molecular evaluation of these mutations is warranted.